Policy, Experience and Change: Cross-Cultural Reflections on Inclusive Education
XVI, 202 p.
Keywords: One of the qualities of this book is the authors’engagement with personal experience. This is part of the contextualising of issues within particular cultural, historical and social contexts. I shall begin the Foreword in the same spirit by recounting an experience that is still a foundation for analysing and developing my own understanding. This h- pened some twenty-five years ago. I was going with Vic Finkelstein, a disabled a- demic and activist, to a seminar, on a hot summer’s day, making our way across the Open University campus in Milton Keynes. The seminar was entitled ‘The Problems of Integration’. Making conversation with Vic I suggested that the seminar sounded int- esting. His response was immediate and direct: no it was not interesting – the problems for disabled people were the problems of segregation, not the problems of integration. As he did often for me, Vic turned understanding on its head and his seemingly simple observation carried ever-increasing ripples of critical questioning. Reading of international developments and of the specifics of education policy, provision and practice across the widely differing circumstances found in different nation states, from the majority as well as the minority world, challenges, deepens and confirms understanding. There are, not surprisingly, considerable diversities and c- monalities, and recurring themes that speak to both – and fire critical questioning. The complexities pretty quickly give food for thought and ring bells of caution. The first for me is the lack of digestion – the impossibility of comprehensive knowledge.